ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MEROKOK PADA ANGGOTA TNI-AD DI YONIF MEKANIS 201/JAYA YUDHA, JAKARTA - Aisyah, Dita Cut; Huda BM, Syamsul; Indraswari, Ratih (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
There are researches from some countries concluding that the prevalence of smoking in military soldiers are relatively higher than civics in many countries. Another, similar research with the scope limitation in Armed Forces whose enlisted in the lower rank, work as army soldiers, and had lower education concluded that the soldiers are tend to be smokers. In Indonesia, even though there is a lot of health information that given to soldier of Indonesian Army, there are still many soldiers that smoke.The purpose of this research is to know the factors that related and affecting to the smoking behavior of Indonesian Army soldiers in the 201th/Jaya Yudha Mechanized Infantry Battalion. The population of this study was the Indonesian Army soldiers in the 201th/Jaya Yudha Mechanized Infantry Battalion, with the population number of 409 people with 50% of estimated case proportion and took 90 respondents that acquired by conducting an accidental sampling technique. Data analysis in this research used univariate, bivariate, and multivariate.The result of this research showed that almost half of the respondents (47,8%) were heavy smokers. Chi square test results showed that the variables attitude (p-value=0,0001), stress scale (p-value=0,021), the belief of smoking related to physical activity (p-value=0,031), exposure of health information (p-value=0,001), the access to get cigarettes (p-value=0,011), family support (p-value=0,0001), and fellow soldiers support (p-value=0,0001) are related with smoking behavior (p<0,05). The unrelated variables to smoking behavior (p>0.05) showed in this research are age, marital status, latest formal education level, military education background, rank, duration of employment in the Indonesian Army, duration of employment in the 201th/JY Mechanized Infantry Battalion, knowledge, and commanders support. The logistic regression test showed that from all variables, fellow soldiers support (p-value=0,003) had the most significant influence of smoking behavior (OR=4,720).